PERAN DINAS KETAHANAN PANGAN, PERTANIAN DAN PERIKANAN KOTA MEDAN DALAM PEMENUHAN KETERSEDIAAN PANGAN KEPALA RUMAH TANGGA PEREMPUAN DI KECAMATAN MEDAN HELVETIA - Annisya Zufais Hasibuan; Wiro Oktavius Ginting (CV. Denasya Smart Publisher, 2025)
The role of government in the realm of public services is an essential element in ensuring equitable food availability through policies and appropriate accessibility especially for female heads of households divorce by death in Medan Helvetia District. This study aims to examine the role of the Medan City Food Security, Agriculture, and Fisheries Service in fulfilling food for female heads of households as a vulnerable group in Medan Helvetia District. The research method used in this study is descriptive qualitative. Data and information collection was carried out using interview, observation, documentation, and literature techniques. The location of the study coincided with the Food Security, Agriculture, and Fisheries Service of Medan City. The informants in this study were the Head of the Service, Secretary of the Service, and Head of the Availability, Stabilization, and Nutrition Division, Assistant Manager of the North Sumatra Provincial Bulog Company and female heads of households in Medan Helvetia District. Data and information were analyzed based on Gade Diva's theory (2009) which includes; The role of government as a regulator, dynamicator, facilitator and catalyst. The results of the study indicate that the Medan City Food Security, Agriculture, and Fisheries Service has made efforts to carry out its role in ensuring food availability for female heads of households in Medan Helvetia District. However, the implementation of policies such as RAD-PG 2022–2024 and programs to support food availability for female heads of households in Medan Helvetia District have not fully strong and satisfied the main target group, namely female heads of households in Medan Helvetia District. Access to digital information such as the Food Management Information System (SIMPANG) is still limited, and the intensity of program socialization has not been effective, but counseling for woman farmers is routine, and coordination with the North Sumatra Province Bulog has not been adaptive enough in improving the dynamics of staple food prices. The Medan City Food Security, Agriculture, and Fisheries Service is advised to strengthen the implementation of RAD-PG 2024-2026 in the future with a participatory and gender-responsive approach, and consider implementing programs that come directly from the relevant agencies for female heads of households as an alternative form of assistance that is more flexible, targeted, and able to guarantee sustainable food access in Medan Helvetia District.